2017
DOI: 10.1212/wnl.0000000000003840
|View full text |Cite|
|
Sign up to set email alerts
|

Decrease in Aβ42 predicts dopa-resistant gait progression in early Parkinson disease

Abstract: Objective: This prospective observational study investigates the role of CSF biomarkers in predicting progression of dopa-resistant gait impairments in Parkinson disease (PD) in the first 36 months from diagnosis.Methods: Quantitative gait analysis was carried out longitudinally using an instrumented walkway (GAITRite) in 108 people with PD and 130 age-matched controls. A subgroup of 44 people with PD underwent lumbar puncture from which a battery of CSF biomarkers was measured: b-amyloid 1-42 and 1-40 (Ab42 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 37 publications
12
71
1
Order By: Relevance
“…This finding is in agreement with previous studies that looked at gait progression in PD and found that pace (step length) decreased over both shorter (ie, 18 months) and longer (ie, 36 months) 49 periods of time. This finding is in agreement with previous studies that looked at gait progression in PD and found that pace (step length) decreased over both shorter (ie, 18 months) and longer (ie, 36 months) 49 periods of time.…”
Section: Does Gait Change Over Time In Pd Converters?supporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with previous studies that looked at gait progression in PD and found that pace (step length) decreased over both shorter (ie, 18 months) and longer (ie, 36 months) 49 periods of time. This finding is in agreement with previous studies that looked at gait progression in PD and found that pace (step length) decreased over both shorter (ie, 18 months) and longer (ie, 36 months) 49 periods of time.…”
Section: Does Gait Change Over Time In Pd Converters?supporting
confidence: 93%
“…We found that over time, walking speed and step length were reduced in both groups, but variability increased. This finding is in agreement with previous studies that looked at gait progression in PD and found that pace (step length) decreased over both shorter (ie, 18 months) and longer (ie, 36 months) 49 periods of time.…”
Section: Does Gait Change Over Time In Pd Converters?supporting
confidence: 93%
“…The exact underlying mechanism of action of nVNS is poorly understood, but an indirect effect mediated through the cholinergic anti‐inflammatory pathway has been postulated through the altered regulation of acetylcholine . Therefore, our aim was to assess the effect of a single dose of nVNS on dopa‐resistant gait characteristics (step time variability and step length variability) in a pilot feasibility study in PD.…”
mentioning
confidence: 99%
“…Gait performance is strongly affected by the overlap between motor and cognitive impairments due to dysfunction of both dopaminergic and cholinergic pathways in PD (Kelly et al, 2015). Besides, low baseline CSF Aβ42 and, to a lesser extent, Aβ40 predicted gait alterations in the first 3 years following diagnosis, suggesting a role for amyloid pathology in gait-cognitive decline (Rochester et al, 2017). An association between axial signs and different aspects of cognition, particularly visuospatial learning and memory, was found in people at intermediate stages of PD (Schneider et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…MoCA scores were also associated with gait performance, freezing of gait, postural stability according to models adjusted for age, sex, education, enrollment site, disease duration, and motor symptoms severity (Kelly et al, 2015). The significant association between MoCA and step time variability is considered additional evidence of interplay between motor and cognitive networks (Rochester et al, 2017). These association may reflect less effective behavioral responses due to attentional control deficits and/or impaired cognitive function.…”
Section: Introductionmentioning
confidence: 99%